Avaliação do software geogebra como instrumento psicopedagógico de ensino em geometria - Nascimento, Eimard Gomes Antunes do (2012)
This current study presents the assessment on Geogebra free software for teaching geometry, as a psycho-pedagogical approach, highlighting resources that facilitate integration and use of program with professors and students’ learning topics. The software can be applied from earlier primary-school students to college ones as well as distance education programs by using internet. Geogebra is a free dynamic mathematic software and multiple-platform for all learning levels, combining geometry, algebra, tables, plotting, graphics, statistics and one-system calculation. The geometry presented was guaranteed and assigned as dynamic geometry and interactive (GDI) that is it, a computer implementation such as: rulers, drawing, square, calipers. Those tools provide motion by keeping construction properties in a static state though, in addition, dynamic motions in order to transforming the computer into a mathematics laboratory where one can perform several technological practices. The study about teaching and learning on geometry and algebra configures itself by means of a descriptive research with exploiting characteristics and almost experimental. The established steps follow as: - re-conception of teaching and learning of mathematics; re-dimension of theories and researches on evaluation. The study of case about assessment of programs on near-by qualitative methodology, in which data and the interface between several presentation of data analysis. We have concluded that the software is innovator and well measured by students and professors who have already used that technology for acquiring knowledge on mathematics and consequently for using in algebra and geometry. Currently, the program is in a long run a great insight and well known throughout.